THE SUPRA-VILLAGE GOVERNMENT’S ELITE DOMINATION IN VILLAGE DEVELOPMENT PLANNING IN BULUKUMBU SOUTH SULAWESI INDONESIA - Nain, Umar (International Journal of Psychosocial Rehabilitation, 2020)
Village development planning plays an important role because, through good planning, it is expected that the implementation of village development is more directed and sustainable and is beneficial to the village community both now and in the future. The purpose of this study was to analyze the dominance of the supra-village government elite in village development planning in Bulukumba Regency. The method used in this study was a qualitative approach with descriptive data analysis of 20 numbers of informants. The results showed that the strengthening of the domination of the supra-village government elite (district and district governments) implied that village development planning was not accommodated in Bulukumba District development planning. Through this dominance, the community experiences the village experiencing powerlessness in village development planning.